ANALISIS SUSEPTIBILITAS MAGNETIK BATUAN ULTRABASA DI DAERAH PASCA PENAMBANGAN NIKEL KECAMATAN WOLO KABUPATEN KOLAKA - waode ulfa intan safitri (Jurnal Rekayasa Geofisika Indonesia, 2020)
Research has been carried out in the post-nickel mining area of Wolo district of Kolaka regency regarding the analysis of the magnetic susceptibility of ultrabasa rocks found the pattern of susceptibility values in the post-mining area is higher ranging from 180 x 10-5 SI to 1019,6 x 10-5 SI and in the mining area the value lower magnetic susceptibility ranges from 172,6 x 10-5 SI to 516,9 x 10-5  SI. The dominant magnetic mineral contained in ultramafic rock samples is hematite (αFe2O3). The rock types contained in ultrabasic rock samples are olivine websterite with magnetic susceptibility value 253,2 x 10-5 SI and lherzolite with magnetic susceptibility value 803,7 x 10-5 SI.Key words: Magnetic Susceptibility, Ultrabasa Rock, Nickel, Wolo District, Kolaka Regency